Detection of Protease Activity Using a Fluorescence-Enhancement Globular Substrate - Edward W. Voss; Creg J. Workman; Mark E. Mummert (BioTechniques)
Bovine serum albumin (BSA) highly derivatized with fluorescein isothiocyanate (FITC, isomer I) served as a fluorescent enhancement substrate to measure protease activity. In the native globular BSA structure, the fluorescence of the lysine-conjugated fluorescein moieties was quenched 98%. Proteolytic digestion of highly derivatized BSA with Pronase® resulted in fluorescence enhancement of 4300%. Both α-chymotrypsin and proteinase K yielded lower but similar fluorescence enhancement values of 2880% and 2800%, respectively. Digestion of the fluorescein-BSA substrate with trypsin, which required basic amino acids for activity, showed fluorescence enhancement of 1480% reflecting the fluorescein-lysine thiocarbamyl linkage. When derivatized substrate was pretreated with a thiol-reducing agent prior to incubation with proteases, a relatively small increase in fluorescence was noted relative to the untreated substrate except in the case of Pronase. The minimum sensitivity of proteolytic activity, based on a comparison of untreated and reduced FITC25BSA was 32 × 10−6 units for 1 ng proteinase K, 1 × 10−3 units for 1 ng α-chymotrypsin and 10 × 10−3 units for Pronase and trypsin (1 ng each). The fluorescence enhancement assay was suited for sensitive intensity measurements or as an endpoint assay to detect protease activity.